Cohort profile: the Finnish Genetics of Pre-eclampsia Consortium (FINNPEC) - Jääskeläinen, Tiina (BMJ Open, 2016)
PURPOSE: The Finnish Genetics of Pre-eclampsia Consortium (FINNPEC) Study was established to set up a nationwide clinical and DNA database on women with and without pre-eclampsia (PE), including their partners and infants, in order to identify genetic risk factors for PE. PARTICIPANTS: FINNPEC is a cross-sectional case–control cohort collected from 5 university hospitals in Finland during 2008–2011. A total of 1450 patients with PE and 1065 pregnant control women without PE (aged 18–47 years) were recruited. Altogether, there were 1377 full triads (625 PE and 752 control triads). FINDINGS TO DATE: The established cohort holds both clinical and genetic information of mother–infant–father triads representing a valuable resource for studying the pathogenesis of the disease. Furthermore, maternal biological samples (first and third trimester serum and placenta) will provide additional information for PE research. Until now, research has encompassed studies on candidate genes, Sanger and next-generation sequencing, and various studies on the placenta. FINNPEC has also participated in the InterPregGen study, which is the largest investigation on maternal and fetal genetic factors underlying PE until now. FUTURE PLANS: Ongoing studies focus on elucidating the role of immunogenetic and metabolic factors in PE. Data on morbidity and mortality will be collected from mothers and fathers through links to the nationwide health registers.